Penerapan Sistem Matrilineal Terhadap Pembagian Warisan - IIusia IIusia; Ahmad Muliadi (Postgraduate of Jayabaya University, 2015)
The purpose of this research is to determine how the application of the matrilineal system of inheritance of land in Minangkabau customary law, as well as the obstacles that arise in the implementation of inheri- tance to property search as well as the efforts made to overcome these obstacles. Minangkabau custom carry on Matrilineal kinship ground. Their life propped by asset which had by ala from generation to genera- tion. That asset proprietary by all family member. This study uses the approach to the typology of normative legal research methods and also takes a historical approach. This study is the perspective of the applica- tion of the matrilineal system of inheritance of land at Minangkabau customary law aims to prated the vulnerable women as compared to men.Keywords: Minangkabau customary law, matrilineal system, inheritance of land